1997
DOI: 10.1001/archsurg.1997.01430290087018
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Counts and Expression of Vascular Endothelial Growth Factor as Prognostic Factors in Node-Negative Colon Cancer

Abstract: Vessel count and expression of VEGF may be useful for predicting distant recurrence in patients with node-negative colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
176
4
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(192 citation statements)
references
References 15 publications
(1 reference statement)
10
176
4
2
Order By: Relevance
“…In colonic carcinomas there is strong evidence for their predictive value (Weidner et al, 1993;Takahashi et al, 1997;Wong et al, 1999). At first glance, this seems to be contrary to our finding of a uniform microvascular architecture in colorectal carcinomas.…”
Section: Discussioncontrasting
confidence: 99%
“…In colonic carcinomas there is strong evidence for their predictive value (Weidner et al, 1993;Takahashi et al, 1997;Wong et al, 1999). At first glance, this seems to be contrary to our finding of a uniform microvascular architecture in colorectal carcinomas.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been previously reported that patients who present with metastases at the time of surgery for primary colon cancer have higher vessel counts than patients with no evidence of metastases (Takahashi et al, 1997). Thus the high MVD observed in our pushing cohort may be a reflection of advanced disease stage.…”
Section: Discussionmentioning
confidence: 59%
“…The use of CD31 MVD analysis as an indicator of angiogenesis is well described. In this study, MVD analysis was performed using digital image analysis in preference to traditional tumour hotspot MVD measurement, which has been shown to be unreliable in assessing net angiogenic activity (Folkman, 1990;Takahashi et al, 1997;Hlatky et al, 2002;Subarsky and Hill, 2003). Our results proved to be reliable and reproducible on statistical testing.…”
Section: Discussionmentioning
confidence: 99%
“…5,[43][44][45][46][47] Some studies have indicated that VEGF expression is an independent prognostic factor in predicting patient prognosis, 5,[43][44][45] while others have reported no such association. 46 Chung et al 47 also showed that VEGF expression was significantly associated with prognosis and hematogenous spread in colorectal carcinoma. Our study showed that VEGF is a useful prognostic marker by correlating significantly with lymphovascular invasion, lymph node status and pT, although it was not an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%